The Development of Career Self-Discovery Skills for Grade 11 Students Using the " Discover Yourself, Discover Your Career " Board Game at Patongprathankiriwat School Hat Yai District Songkhla Province. - สูดี, ตัสนีม; ทองสิพพัญญู, ถิรพล; ไชยพันธุ์, ไหมไทย; วงประไพโรจน์, จันทร์จิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to 1) develop career self-exploration skills among secondary school students through the implementation of the “Discover Yourself, Discover Your Career” board game to achieve the predetermined proficiency criteria, 2) examine the effects of this board game on students’ career self-exploration skills, and 3) assess students’ satisfaction with the use of the board game. The sample comprised 25 Grade 11 students from Class 1, Semester 1, Academic Year 2025 at Phatongprathankirivat School, Hat Yai District, Songkhla Province, selected via cluster sampling. The research instruments included: 1) a guidance learning management plan focused on self-exploration for career decision-making, 2) a career self-exploration skills questionnaire administered pre- and post-intervention, 3) the “Discover Yourself, Discover Your Career” board game consisting of a game board, dice, player tokens, and 28 question cards, and 4) a satisfaction questionnaire. Data were analyzed using descriptive statistics, namely percentage, mean, and standard deviation.The results indicated that 1) following the intervention, 84% of students exhibited clarity in career selection, surpassing the established benchmark; 2) students’ career self-exploration skills were at a moderate level prior to the intervention (ˉˉ x̄=3.39, S.D. = 0.60), but significantly increased to a high level post-intervention (x̄= 4.52, S.D. = 0.55); and 3) students reported the highest levels of satisfaction with the board game across all evaluated domains. These findings substantiate the efficacy of the “Discover Yourself, Discover Your Career” board game as an innovative pedagogical tool for enhancing career self-exploration skills in upper secondary education.